Simulation of two-dimensional attainable regions and its application to model digester structures for maximum stability of anaerobic treatment process. (15th October 2019) - Abunde Neba, F.; Asiedu, Nana Y.; Addo, Ahmad; Morken, John; Østerhus, Stein W.; Seidu, Razak
Abstract: Unlike high-rate anaerobic digesters that employ some mechanism to retain microbial sludge mass, low-rate systems use sufficiently long hydraulic retention times to ensure process stability, which becomes economically unattractive for treating large quantities of waste. This study presents the use of attainable region to develop a new strategy to enhance the stability of low-rate digesters. By considering three digestion cases, diary manure only (batch 1) or diary manure with granular (batch 2) or lagoon (batch) sludge as innoculum, the following findings were obtained. (1) For a given concentration of volatile acids in an anaerobic digester, higher concentrations of methanogenic archae can be attained using a digester structure (combination of different digesters) as opposed to single digester. (2) For a given digested substrate, a change in the source of inoculum results in a change in the limits of achievability by the system (attainable limits for batches 1, 2 and 3 were 46.486(g/L) 2, 5.562(g/L) 2 and 0.551(g/L) 2, which resulted in performance improvements of 118.604%, 175.627% and 200.436% respectively), and hence optimal digester structure. The evidence from this study suggests that the technique can be used to simultaneously improve process stability, define performance targets and propose digester structures required to achieve a given target. Highlights: A geometric optimization approach to improve stability in low-rate digesters. The technique defines both performance targets and optimal digester structures. Use of digester structures improve process stability compared to single digesters. Methanogenic archae are more viable in digester structures than in single digesters. A change in the source of inoculum results in different optimal digester structures.